2012
DOI: 10.1002/jid.1709
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and disability: A vicious circle? Evidence from Afghanistan and Zambia

Abstract: Disability and poverty have a complex and interdependent relationship. It is commonly understood that persons with disabilities are more likely to be poor and that poverty may contribute to sustaining disability. This interdependency is revealed not only through an examination of poverty in terms of income but also on a broader scale through other poverty related dimensions. Just how robust is this link? This paper compares data collected from household surveys in Afghanistan and Zambia, and explores the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 41 publications
8
96
0
3
Order By: Relevance
“…Students with TSCI fail to continue with school due to the restrictive environment and newly married and young parents fail to meet the needs for their families. Consequently, poverty strikes the family, children’s education is deterred and long term poor quality of life is inevitable hence a poverty-disability viscous cycle [28]. In this age group some are injured in the process of establishing a family or soon after marriage, which affects their sexual life leading to massive psychological disturbance [29].…”
Section: Discussionmentioning
confidence: 99%
“…Students with TSCI fail to continue with school due to the restrictive environment and newly married and young parents fail to meet the needs for their families. Consequently, poverty strikes the family, children’s education is deterred and long term poor quality of life is inevitable hence a poverty-disability viscous cycle [28]. In this age group some are injured in the process of establishing a family or soon after marriage, which affects their sexual life leading to massive psychological disturbance [29].…”
Section: Discussionmentioning
confidence: 99%
“…These may lead to higher health expenditures. Trani and Loeb (2010) also show that on average, 'persons with severe or very severe disabilities spent 1.3 times more on healthcare than nondisabled respondents' (p. 36). show that households with disabilities have a higher ratio of medical to total expenditures in nine out of 15 countries while WHO-World Bank (2011) finds that persons with disabilities are more likely to experience catastrophic health expenditures.…”
Section: Morbidity and Healthcare Expendituresmentioning
confidence: 92%
“…3 However, Eide et al (2003a) and Trani and Loeb (2010) find no significant difference in Zimbabwe and Afghanistan/ Zambia, respectively. find a significant difference in the rate of asset deprivation in only four of 15 LMICs.…”
Section: Materials Wellbeingmentioning
confidence: 95%
See 1 more Smart Citation
“…Some recent research in LMICs has consistently found that disability is associated with a higher likelihood of experiencing simultaneous multiple deprivations (multidimensional poverty) (Hanass-Hancock and McKensie 2017; Mitra et al 2013;Trani and Cunning 2013;Trani et al 2015Trani et al , 2016. In contrast, some research using traditional poverty indicators (consumption expenditures and asset ownership) paints a mixed picture (Filmer 2008;Mitra et al 2013;Trani and Loeb 2010).…”
Section: Motivationmentioning
confidence: 99%